The Beauty of Preaching: God's Glory in Christian Proclamation - Pasquarello, Michael (William B. Eerdmans Publishing Company, 2020)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Foreword by Will Willimon -- Preface -- Acknowledgments -- Introduction: Reclaiming Beauty -- A Spirited Beauty -- An Eschatological Beauty -- An Invitation to Beauty -- 1. Saving Beauty -- A Useless Beauty -- The Joy of Preaching -- A Homiletical Aesthetic -- 2. Seeing Beauty -- Remembering the Beauty of the Unnamed Woman's Act in Preaching -- A Homiletical Aesthetic -- 3. A Converting Beauty -- Seeking Beauty -- A Humble Word -- Surprised by Beauty -- To Love the Beauty of the Word -- Seeing the Beauty of the Creator in the Creation -- A Homiletical Aesthetic -- 4. A Spoken Beauty -- Trinitarian Beauty and Preaching -- Preaching as the Beauty of Wisdom -- The Delight of Preaching -- Incarnate Beauty -- Preaching as Humble Speech -- Preaching the Melody of Love -- 5. A Simple Beauty -- The End of Preaching: Holiness and Happiness in God -- Holy Preaching, Holy Living -- The Beauty of Preaching and the Poor -- Preaching in the Beauty of Holiness -- A Homiletical Aesthetic -- 6. A Strange Beauty -- Prophetic Beauty -- Poetic Beauty -- Magnificat: The Beauty of Mary's Praise -- Conclusion: Beauty, Now and Then -- Preaching for the Praise of God's Glory -- A Homiletical Aesthetic -- The Blessed Uselessness of Preaching -- A Homiletical Aesthetic for a Pilgrim People -- Proclaiming the Way of Love -- A Sacramental Beauty -- Bibliography -- Index of Names and Subjects -- Index of Scripture References.